Consumer purchase intentions toward counterfeit branded products among Generation Y in Malaysia / Nur Izza Zafierah Zuhaili - Zuhaili, Nur Izza Zafierah (Faculty of Business and Management, 2019)
Counterfeiting is a major issue for companies, governments and consumers. Promotional media and gender have been shown to influence purchase and shopping channel choice. The purpose of this paper is to better understand the role of social influence, status consumption, brand image, novelty seeking, price quality inference and integrity on consumer purchase intentions towards counterfeit branded products among Generation Y. Theoretical framework included is adopted from Krishnan (2017). A survey was administered using a convenience sample of Generation Y in Bangi Sentral, Bandar Baru Bangi, Selangor. A total of 176 surveys were used for analysis. The data were factor analysed using Statistical Package for the Social Sciences (SPSS) statistical software and a structural equation model was developed to test the hypotheses. The results indicate that while the social influence factor, status consumption and brand image significantly influence consumer purchase intentions. Meanwhile, novelty seeking, price quality inference and integrity only indicated no significant relationship. Finally, in order to curb counterfeiting, more awareness can be done and improve the brand image of a product.